Rainbow revisited [compact disc] - Ntuli, Thandi (International Anthem Recording Co., 2023)
South African pianist Thandi Ntuli traveled to Los Angeles in 2019, where she recorded this album of bare, explorative piano and voice pieces at a Venice Beach studio with International Anthem artist Carlos Ni?o in the producer chair. An absolutely stunning, intimate listen, with Ntuli's prowess as a pianist and singularity as a vocalist on vivid display as much as her fearlessness, vulnerability and adventurousness during occasional experiments with synthesizers and percussion. Ni?o colors open minimalist soundscapes with overdubbed percussion, cymbals and plants.